Antioxidative effect of Melastoma Malabathticum L Extract and Determination of its Bioactive Flavonoids from Various Location in Malaysia by RP-HPLC with Diode Array Detection - Sundram Karupiah and Zhari Ismail (Journal of Applied Pharmaceutical Science, 2013)
A rapid and specific RP-HPLC method with DAD at 30°C was developed and validated for the determination of quercetin (QN) and kaempferol (KMP) as marker compounds in the extract of Melastoma malabathrichum leaves. Separation was performed using Hypersil GOLD C8 column with acetonitrile - 0.1% phosphoric acid (40:60v/v) as a mobile phase with DAD detection at 370 nm. The developed method showed satisfactory reproducibility and recovery and the method was successfully applied in the determination of QN and KMP as marker compounds in MM leaves collected from different parts of Malaysia and was found to be simple, rapid and efficient. The antioxidant activity of MM of 3 different solvent extracts (methanol, ethyl acetate, chloroform) were evaluated using β-carotene bleaching method. A variation in antioxidant activities, ranging from 44.41% to 83.28% was observed and the antioxidative potency of the 3 different solvent extracts was comparable to that of butylated hydroxytoluene (BHT). The results showed that MM extracted by different solvents exhibited varying degree of antioxidant properties.
Keywords: Melastoma malabathricum, HPLC-DAD